2018
DOI: 10.1017/qua.2018.40
|View full text |Cite
|
Sign up to set email alerts
|

Collagen stable isotopes provide insights into the end of the mammoth steppe in the central East European plains during the Epigravettian

Abstract: Higher δ15N values in bone collagen of mammoth (Mammuthus primigenius) compared with coeval large herbivores is a classic trait of the mammoth steppe. An exception applies to the Epigravettian site of Mezhyrich (ca. 18–17.4 ka cal BP) in the central East European plains, where mammoth bones have δ15N values equivalent to or in a lower range than those of horse specimens (Equus sp.). We expanded our preliminary dataset to a larger sampling size of mammoth, other large herbivores, and carnivores from contemporan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…Several hypotheses have been proposed to explain this feature, including consumption of forage in arid microhabitats (Bocherens, 2003;Iacumin et al, 2000;Kuitems et al, 2012), consumption of plants fertilized with dung , and/or selection of specific plants or plant parts during forage (Kuitems et al, 2012;. Mammoth core niche overlaps with horse both preand post-LGM, suggesting that some horse also exploited this distinct niche, as has been previously observed in both the INF & pre-LGM and the post-LGM time bins (Drucker et al, 2015(Drucker et al, , 2018Schwartz-Narbonne et al, 2015).…”
Section: Pleistocene Herbivore Nichesmentioning
confidence: 77%
See 1 more Smart Citation
“…Several hypotheses have been proposed to explain this feature, including consumption of forage in arid microhabitats (Bocherens, 2003;Iacumin et al, 2000;Kuitems et al, 2012), consumption of plants fertilized with dung , and/or selection of specific plants or plant parts during forage (Kuitems et al, 2012;. Mammoth core niche overlaps with horse both preand post-LGM, suggesting that some horse also exploited this distinct niche, as has been previously observed in both the INF & pre-LGM and the post-LGM time bins (Drucker et al, 2015(Drucker et al, , 2018Schwartz-Narbonne et al, 2015).…”
Section: Pleistocene Herbivore Nichesmentioning
confidence: 77%
“…Pires et al (2015) suggested a higher degree of functional redundancy on the Pleistocene mammoth steppe than in the modern African savannah network and Davis (2017) demonstrated that Pleistocene North America had more functional redundancy than present North America. Other studies have noted niche overlap and species dietary plasticity on the mammoth steppe based on isotopic analysis Bocherens et al, 2015;Drucker et al, 2015Drucker et al, , 2018Fox-Dobbs et al, 2008;Münzel et al, 2016;Schwartz-Narbonne et al, 2015) and tooth wear studies , albeit not describing this as functional redundancy. Pleistocene niche overlap also occurred outside the mammoth steppe (see Lanoë et al, 2017).…”
Section: Functional Redundancy and Resource Partitioningmentioning
confidence: 99%
“…Bone collagen can also be analysed for its stable isotope compositions, which are powerful tools for investigating past ecology and terrestrial environments, and have been employed widely in Late Pleistocene archaeological research [35][36][37][38][39][40][41] . In this study we use carbon (δ 13 C), nitrogen (δ 15 N) and sulphur (δ 34 S) isotope ratios in reindeer bone collagen to examine paleoenvironmental conditions during the period of human activity at Kastelhöhle-Nord and Y-Höhle.…”
Section: Radiocarbon and Stable Isotope Analysesmentioning
confidence: 99%
“…Dietary δ 13 C values are also influenced by atmospheric CO 2 δ 13 C value and concentration, and by environmental parameters such as temperature, moisture availability and density of vegetation cover 35,[44][45][46] . Bone collagen δ 15 N values are linked to both dietary specialisation 41,47,48 and to environmental conditions [29][30][31][32] . Soil and plant δ 15 N values are influenced by climatic variables such as temperature and precipitation, mediated through soil processes 49,50 .…”
Section: Radiocarbon and Stable Isotope Analysesmentioning
confidence: 99%
“…Faunal δ 34 S has typically been linked to animal mobility (Drucker et al 2012 , 2018 ; Jones et al 2018 ; Wißing et al 2019 ), as soil sulphur is primarily derived from mineral weathering of underlying lithology and is therefore spatially variable (Nehich 2015 ). However, soil δ 34 S can be strongly modified by changing bacterial reactions related to alterations in soil moisture content and oxygen status (Thode 1991 ; Mandernack et al 2000 ).…”
Section: Discussionmentioning
confidence: 99%